Strength Analysis of Gearbox for Urban Rail Train based on Abaqus - Fan Naize; Li Bowen; Xu Dawei; Li Liangyu; Liu Jie (Jixie chuandong)
In order to optimize the design method of the gear transmission system for urban rail transit trains in China，the mechanical strength check of the gear transmission system for urban rail trains in actual operation is performed.The loading scheme is formulated according to the design input.The gear transmission system model is created by using the 3D modeling software SolidWorks，and it is imported into the finite element analysis software Abaqus for finite element calculation.The calculation results show that the mechanical strength of the gearbox meets the requirements of train operation，and the type test results prove the credibility of the finite element calculation method.The research work has important reference value for the application of the finite element analysis method in the development and design of urban rail train gearbox.